An assessment of the clinical equivalence of valproate chrono and extended release divalproex formulations - Rajesh B; Ashalatha R; Sarma Sankara; Radhakrishnan K (Annals of Indian Academy of Neurology, 2007)
Objective: No guideline currently exists to choose the clinically equivalent dose of divalproex extended release (ER) formulation while switching over from valproate chrono formulation. To address this issue, we evaluated the serum valproate concentration following switch over from valproate chrono to divalproex ER in persons with epilepsy. Materials and Methods: An open label study was conducted in two parts, each for a period of two months. During Part I, patients on regular twice-daily dose of valproate chrono were switched over to once daily divalproex ER (DESVAL ER ® ) based on the dose escalation recommended when switching over from divalproex DR to ER formulation as the guideline. During Part II, we switched from valproate chrono to divalproex ER with same dosage. Serum valproate concentration, seizure frequency and side effects were assessed serially for two months after changeover and compared with the preswitch data. Results: During Part I, compared to the baseline level, there was a significant increase in mean serum valproate level at two months (67.0 ± 28.4 mg/ml versus 91.9 ± 3.5 mg/ml, P 0.004). With the same dose conversion during Part II, the mean valproate level did not significantly differ before and after the switch (81.5 mg/dl versus 85.7 mg/dl, P 0.08). The mean monthly seizure frequencies and serum ammonia levels did not change during either part. No significant adverse effects occurred. Conclusion: The results of this open label study with small number of patients need to be replicated among larger patient sample through a randomized control design before recommending same dose conversion from valproate chrono to divalproex ER without change in efficacy and tolerability,